What can the CNO neutrinos flux measurement done by Borexino say about 40K geoneutrino flux?. (December 2020) - Sinev, V; Bezrukov, L; Karpikov, I; Kurlovich, A; Mezhokh, A; Silaeva, S; Zavarzina, V
Abstract: Borexino collaboration announced the observation of CNO neutrinos flux. Its value appeared larger than expected in case of the Sun high metallicity model. This could be regarded as evidence of large potassium content inside the Earth. The potassium abundance can reach (1.5 ± 1.0)% in the whole Earth and the Earth heat flux can be at the level of 200-300 TW. To resolve the problem a new experiment is demanded with a detector similar to Borexino one but better in backgrounds or a detector with another techniques of neutrino measurement, for example on base of 115 In.